Kabankalan City Accommodation Industry: Sustainable Business Attitudes and Practices - ALFARAS, Kimberly A.; ALFARAS, Riza Stephanie A. (Journal of Environmental Management and Tourism, 2021)
This paper explores the sustainable business attitudes and practices of the 74 employees and 294 guests of the different accommodation establishments at Kabankalan City. This paper collated data on employees' and guests’ sustainable business attitudes and practices using an adapted instrument of Raderbaeur (2011). Results demonstrated that the employees and guests experienced high extent of sustainable business attitudes and highly practiced sustainability. Furthermore, when employees were categorized according to their sex, age, and civil status profile, a non-significant result was revealed on the extent of sustainable business attitudes. However, when guests were grouped according to their civil status profile, a highly significant result was revealed on the extent of sustainable business attitudes, and guests significantly differed when grouped according to sex, age, and highest educational attainment. Likewise, a not significant result revealed on the extent of employees' and guests’ sustainable business practices across all profile characteristics. Finally, sustainable attitudes were significantly associated with sustainable business practices. Employees and guests possessed a right positive, sustainable business attitude and were able to translate it into their actions, thus practicing sustainability.